The differential diagnostic value of left ventricular segmental myocardial strain in cardiac amyloidosis and non-obstructive hypertrophic cardiomyopathy - Yang LIU; Fangmin MENG; Nianwei ZHOU; Lina LUAN; Cuizhen PAN; Xianhong SHU (Zhongguo Linchuang Yixue)
ObjectiveTo explore the difference of the left ventricular global longitudinal strain (GLS) and the segment strains between cardiac amyloidosis (CA) and non-obstructive hypertrophic cardiomyopathy (HCM). MethodsTwenty patients with immunoglobulin light chain cardiac amyloidosis (AL-CA) as CA group and 20 patients with non-obstructive HCM selected as controls (HCM group) were enrolled from January 2016 to April 2022 in Zhongshan Hospital, Fudan University. All patients underwent two-dimensional speckle tracking echocardiography (2D-STE). The left ventricle GLS and the segmental strains were calculated. The values of these strains to distinguish AL-CA from HCM were analyzed by receiver operating characteristic (ROC) curves and logistic regression analysis. ResultsIn the CA group, the GLS parameters (3P, 4Ch, 2Ch, 3Ch), as well as the left ventricle segmental strains (MID-ANT/LAT, MID-INF/SEPT, BASAL-ANT/LAT, BASAL-INF/SEPT, MID-ANT, MID-INF, BASAL-ANT, BASAL-INF, MID-INF/LAT, BASAL-ANT/SEPT, and BASAL-INF/LAT) were all lower than those in the HCM group (P＜0.01). ROC results showed that GLS(4Ch), GLS(2Ch), GLS(3Ch), GLS(3P), BASAL-ANT/LAT, BASAL-INF/SEPT, BASAL-ANT, BASAL-INF, BASAL-ANT/SEPT and BASAL-INF/LAT had good efficacy in distinguishing AL-CA from HCM. Logistic regression analysis showed that BASAL-ANT/LAT was an independent factor in distinguishing AL-CA from HCM (P＜0.01). The consistency of test results was good. ConclusionsThe left ventricular segmental myocardial strains show good efficacy in distinguishing AL-CA from HCM, and BASAL-ANT/LAT has highest application value.